IFN-γ-Driven macrophage responses in the immunity to Mycobacterium tuberculosis and Mycobacterium leprae - Imran, Mohd; Alshrari, Ahmed S.; Khan, Abida; Alzahrani, Abdullah R. (Frontiers in Cellular and Infection Microbiology, 2025)
Interferon-gamma (IFN-γ) is a key stimulator of macrophage defense against Mycobacterium tuberculosis (Mtb) and Mycobacterium leprae (M. leprae). Both pathogens adopt measures to circumvent the effects of the immune system, weakening the impact of IFN-γ and enabling them to survive in the cells. This review synthesizes how IFN-γ overdose transacts the JAK/STAT1-IRF1-transmitter to encourage maturation of phagolysosomes, reactive oxygen and nitrogen product generation, LC3-associated phagocytosis (LAP), autophagy, and improved antigen presentation and juxtaposes these pathways in tuberculosis and leprosy. We also explain the mechanisms by which mycobacteria counter this axis, including receptor downregulation, induction of IL-10/SOCS, type I INF antagonism, and the impact of miRNA. Additionally, we assessed the translational application, emphasizing its benefits, potential risks, and sources of variability. Additionally, we discuss biomarker strategies related to IFN-γ activity, such as gene signatures associated with HIF-1 and active IFN-γ measurements, which could aid in selecting patients and tracking their treatment progress. The results show that macrophage-related processes are important for the treatment and diagnosis of TB and leprosy when they occur simultaneously. This highlights the need for safe and effective treatments that focus on the host and balance the protective and harmful effects of IFN-γ.